A Novelty Massive MIMO Channel Model Based on the Birth‐and‐Death Process of Spatial Multipath Cluster. Issue 10 (7th October 2020) - Lu, Yanping; Zhang, Yongjun; Fu, Liqin; Qiu, Jiahui; Liu, Kai; Li, Qichang
Abstract: In this paper a novelty Massive Multiple Input Multiple Output (MIMO) channel model based on the birth‐and‐death process of multipath clusters is proposed. First, Massive MIMO measurements are conducted in typical outdoSor scenarios with the bandwidth of 100 MHz at frequencies of 1.4725 and 6 GHz, respectively, following with the investigation of radio propagation characteristics over antenna array. Then we research on the subchannel correlation and nonstationary based on the channel sounding experiments. Furthermore, we build up a Markov chain to characterize the birth‐and‐death process of the multipath clusters over the array, which is helpful to bring deeply insight into the cluster evolution over the antenna array axis. And the analysis results are consistent with the theory of the cluster's visible region. At last, the paper systematically demonstrates how does the spatial correlation influence the capacity of the communication system. The whole research work aims to contribute the radio channel modeling of the fifth‐generation (5G) Massive MIMO communication system. Key Points: Wideband multiantenna measurements are taken for Massive MIMO channels Cluster's birth‐and‐death process over the antenna array is studied to characterize nonstationary of Massive MIMO channel Channel capacity is studied to have an insight into the degradation caused by antenna correlation